An exergy-based investigation on hydrogen liquefaction plant-exergy, exergoeconomic, and exergoenvironmental analyses. (10th February 2019) - Ansarinasab, Hojat; Mehrpooya, Mehdi; Sadeghzadeh, Milad
Abstract: In this study, a conventional hydrogen liquefaction process is comprehensively analyzed. The studied hydrogen liquefaction process is consisted of two independent MR (Mixed Refrigerants) refrigeration cycles. In order to evaluate the liquefaction process and obtain valuable and noteworthy results, the process is examined through a comprehensive exergy based analyses. The exergy based analyses includes conventional exergy analysis to examine the performance of the liquefaction process, exergoeconomic analysis to obtain the effect of cost and economy on the performance, and exergoenvironmental analysis to provide beneficial information about the mutual effect of system's performance and environmental conditions. In addition, a sensitivity analysis is provided to assess and determine the mutual interaction among costs, environmental effects of each component, and the amount of exergy destruction. From the results, it is shown that the first refrigeration cycle exergy efficiency is obtained about 67.53% and the second refrigeration stage exergy efficiency is calculated about 52.24%. The whole hydrogen liquefaction process is exergy efficiency is 55.47%. The specific energy consumption (SEC) of this process is equal to 1.102 kWh/kgLH2 . The total performance coefficient of the total process is 0.1797 which is higher than other reported articles. It is recommended from the Exergoeconomic and Exergoenvironmental analyses that the employed turbo-expanders and compressors are in priority for possible modification of the total process in the future. Highlights: A new hydrogen liquefaction process is investigated by exergy based analysis methods. Two independent mixed refrigerant cycles are used for hydrogen liquefaction. The process is evaluated by a 3E (exergy/exergoeconomic/exergoenvironmental) analysis.